Advances in Extracorporeal Membrane Oxygenation Volume 3 - Firstenberg, Michael S. (IntechOpen, 2019)
Extracorporeal membrane oxygenation is an effective tool for managing patients with severe acute cardiogenic shock and/or respiratory failure. With emphasis on teamwork and adherence to guidelines, protocols, and objective tools to assist in patient selection, management, and weaning, outcomes have improved. Nevertheless, every aspect of supporting patients who require extracorporeal support remains a challenge - with many unanswered questions. The goal of this text, as a supplement to the previous editions on this rapidly evolving topic, is to provide the reader with a more in-depth review of some of the ongoing issues in this field. Topics ranging from administrative aspects to developing a program, nursing issues, ethical concerns, and a variety of clinical topics are discussed at length.